Dermoscopy of Onychomycosis: A Systematic Review - Noureddine Litaiem; Emna Mnif; Faten Zeglaoui (Mattioli1885, 2023)
Introduction: Onychomycosis represents a global burden accounting for about 50% of nail consultations. Several studies have tried to assess the dermoscopic features of onychomycosis. With the multiplication of papers, several "new" dermoscopic signs keep being added leading to some inconsistency in onychoscopic terminology. Objective: This study aimed to summarize the existing literature on the dermoscopic features of onychomycosis and propose a unified onychoscopic terminology. Methods: The literature search was performed using PubMed and Scopus databases up to October 30, 2021 to identify eligible contributions. In total, 33 records (2111 patients) were included. Results: The main dermoscopic signs of onychomycosis are "ruin appearance", "longitudinal striae" and "spikes" on the proximal margin of onycholytic areas, with a specificity of 99.38%, 83.78%, and 85.64% respectively. The "aurora borealis" sign had the highest sensitivity and specificity. Conclusions: The current review provides a framework for issues related to the onychoscopic terminology of onychomycosis and is intended to serve as an aid for students, teachers, and researchers. We proposed a unifying terminology to describe dermoscopic signs of onychomycosis. Dermoscopic signs of onychomycosis show good specificity and are useful in distinguishing nail psoriasis, trauma, and onychomycosis. It helps differentiate fungal melanonychia from nail melanoma, nevi, and melanocytic activation.